LONG-TERM EVALUATION OF THE SAFETY AND EFFECTIVENESS OF NEURAL STEM CELL TRANSPLANTATION FOR CHRONIC THORACIC SPINAL CORD INJURY - Harmin; Maharani, Hanisa Aulia (Journal of Stem Cell Research and Tissue Engineering, 2025)
Spinal cord injury (SCI) is a debilitating neurological condition that leads to partial or complete loss of motor and sensory function, depending on the injury’s severity and location. Conventional therapies focus on surgical stabilization, prevention of secondary damage, and rehabilitation. However, these approaches often fall short in restoring long-term functionality. In recent years, cell-based therapies have emerged as promising alternatives, particularly those involving neural stem cells (NSCs). This literature review explores the long-term safety and effectiveness of NSC transplantation for chronic thoracic SCI, based on studies published between 2010 and 2025. Research shows that fetal-derived NSCs, such as HuCNS-SC, demonstrate a high safety profile and low risk of tumor formation due to their committed neural lineage. Clinical trials report early signs of motor improvement and reduced spasticity in chronic SCI patients following transplantation. Additionally, mesenchymal stem cells (MSCs) have shown the ability to migrate to injury sites and exert therapeutic effects, though these benefits tend to be short-lived. The post-injury inflammatory microenvironment poses a significant barrier to the success of NSC therapies by impairing stem cell differentiation and survival. Therefore, immunosuppressive regimens are often employed to enhance NSC efficacy by creating a more supportive environment. Overall, while both NSCs and MSCs offer promising avenues for SCI treatment, long-term recovery likely requires multimodal approaches that address both neural regeneration and immune modulation. Continued research is essential to optimize these therapies and translate them into effective clinical treatments for patients with chronic SCI.